2020
DOI: 10.1371/journal.pgen.1008897
|View full text |Cite
|
Sign up to set email alerts
|

c-di-GMP inhibits LonA-dependent proteolysis of TfoY in Vibrio cholerae

Abstract: The LonA (or Lon) protease is a central post-translational regulator in diverse bacterial species. In Vibrio cholerae, LonA regulates a broad range of behaviors including cell division, biofilm formation, flagellar motility, c-di-GMP levels, the type VI secretion system (T6SS), virulence gene expression, and host colonization. Despite LonA's role in cellular processes critical for V. cholerae's aquatic and infectious life cycles, relatively few LonA substrates have been identified. LonA protease substrates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…But, the mechanisms or external signals that induce the secretion activity is not fully known. LonA belongs to the superfamily of ATPases that repress the T6SS and influence T6SS-dependent killing phenotypes differently in V. cholerae strains with high and low levels of c-d-GMP (Joshi et al, 2020 ).…”
Section: Regulation Of Secretion Systems (T2ss/t3ss/t6ss)mentioning
confidence: 99%
“…But, the mechanisms or external signals that induce the secretion activity is not fully known. LonA belongs to the superfamily of ATPases that repress the T6SS and influence T6SS-dependent killing phenotypes differently in V. cholerae strains with high and low levels of c-d-GMP (Joshi et al, 2020 ).…”
Section: Regulation Of Secretion Systems (T2ss/t3ss/t6ss)mentioning
confidence: 99%
“…Studies of human-derived strains identify two primary TFs for T6 activation (19)(20)(21)(22)(23). T6 control in pandemic strains (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…C6706) requires QstR (Quorum-Sensing and TfoX-Dependent Regulator), which integrates multiple external cues (24)(25)(26)(27), and contains a DNA binding domain postulated to interact with a presumptive CRE of the major T6 gene cluster (20,24). T6 regulation in non-pandemic strain V52, which causes mild disease, requires TfoY, modulatable by intracellular signals (22,23). How QstR and TfoY control T6 transcription remains elusive, with no T6 CRE yet described.…”
Section: Introductionmentioning
confidence: 99%
“…Most knowledge about Lon has been obtained by studying bacterial Lon orthologs. In Escherichia coli , Lon specifically degrades several stress-induced regulators ( Griffith et al, 2004 ; Langklotz and Narberhaus, 2011 ; Mizusawa and Gottesman, 1983 ), metabolic enzymes ( Arends et al, 2018 ) as well as antitoxins of toxin-antitoxin systems ( Muthuramalingam et al, 2016 ), and in several pathogenic bacteria, Lon was shown to degrade regulators of pathogenicity ( Joshi et al, 2020 ; Puri and Karzai, 2017 ), thus playing important roles in the regulation of virulence pathways. In the alpha-proteobacterium Caulobacter crescentus , the number of identified Lon substrates to date is small, however, Lon is known to impact cell cycle progression by degrading essential cell cycle regulators.…”
Section: Introductionmentioning
confidence: 99%